O discurso sobre a sexualidade feminina : subjetividades e identidades em construção - Araújo, Karen Dominique Rodrigues de (2018)
The paper deals with the discourse of feminine sexuality in the present time. We discuss the discursive functioning of the subject in question and analyze in what extent these practices refer more to a conservative discourse or a progressive discourse. From the theoretical-methodological device of Pêcheuxtiana Discourse Analysis, we analyze 18 publications that circulate in the social network Facebook, along with the most relevant comments made to them. The temporal cut of these texts comprises the period from 2014 to 2018. The discourses are exposed; the chaining of the signifiers and the sliding movement between them; the effects of senses produced; the relations between the discursive formations (FD) and the constructed images about the woman, the man and the relationships with commitment and without commitment. The following discursive objects stand out: ideal woman to marry; faithfulness and betrayal; sex, pleasure, feelings and reproduction; sex on the first date; and freedom from casual sexual relations. The discourse of feminine sexuality is based on relations of conflict. Conservative discourse, which for a long time has remained as a dominant discourse, is always in tension with the dominated discourse, the progressive discourse. Because of this plurality of discourses, female sexuality can not be thought as homogeneous, universal and stable. It is in constant formation, marked by heterogeneity and contradiction. Thus, when thinking about sexual identity, it is necessary to think of a multiplicity of identities that constitute the female subject. Key words: discourse, feminine sexuality, identity, subjectivity and social network.